Hydrothermal synthesis of Zinc oxide (ZnO) nanotubes and its electrophoretic deposition on nickel filter - Ipeksac, Tugba; Kaya, Figen; Kaya, Cengiz (ELSEVIER SCIENCE BV, 2013)
Multi-walled ZnO nanotubes were synthesized by a simple hydrothermal treatment of nanowire-rod like ZnO powders without use of any catalysts, plate or substrates. ZnO nanotube structures were synthesized at a low temperature of 180 degrees C in an aqueous solution including nanowire-rod like ZnO powders and hydrogen peroxide. The synthesized ZnO nanotubes were coated on 3D nickel filters by electrophoretic deposition (EPD) technique. It is shown that the obtained multi-walled ZnO nanotubes show antibacterial behavior and have variable inner diameters of 5-17 nm, outer diameters of 10-22 nm and 8-9 layers. It is suggested from the results obtained that formation of zinc oxide nanotubes from nanowire-rod like ZnO structures can be explained with Kirkendall-type diffusion. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Nanoparticles; Ceramics; Hydrothermal synthesis; Zinc oxide; Electrophoretic deposition; ANTIBACTERIAL ACTIVITY; GROWTH-MECHANISM; Materials Science; Physics